2021
DOI: 10.1016/j.cmi.2021.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Serious bradycardia and remdesivir for coronavirus 2019 (COVID-19): a new safety concerns

Abstract: Objectives In recent clinical trials some cardiac arrhythmias were reported with use of remdesivir for COVID-19. To address this safety concern, we investigated whether use of remdesivir for COVID-19 is associated with an increased risk of bradycardia. Methods Using VigiBase®, the World Health Organization Global Individual Case Safety Reports database, we compared the cases of bradycardia reported in COVID-19 patients exposed to remdesivir with those reported in COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
89
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 15 publications
6
89
3
3
Order By: Relevance
“…Analyzing the time of occurrence of our cardiac AEs, our findings showed that the mean time to the onset specific for cardiac events was 3.3 days. Touafchia et al showed in their pharmacovigilance study a slightly shorter median onset of bradycardia (2.4 days; range 1–6) but results with regard to the comparison between remdesivir and hydroxychloroquine are similar to our findings [ 27 ]. Our study suggests an increased risk of reporting a cardiac event with remdesivir compared to other well-known cardiotoxic medicines used in the COVID-19 pandemic, such as azithromycin or hydroxychloroquine.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Analyzing the time of occurrence of our cardiac AEs, our findings showed that the mean time to the onset specific for cardiac events was 3.3 days. Touafchia et al showed in their pharmacovigilance study a slightly shorter median onset of bradycardia (2.4 days; range 1–6) but results with regard to the comparison between remdesivir and hydroxychloroquine are similar to our findings [ 27 ]. Our study suggests an increased risk of reporting a cardiac event with remdesivir compared to other well-known cardiotoxic medicines used in the COVID-19 pandemic, such as azithromycin or hydroxychloroquine.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, it has also pointed out that these fatal cardiac events are to be referred to hospitalized COVID-19, a clinical condition that itself is predictive of cardiovascular risk with a fatal outcome [ 35 , 36 , 37 ]. However, our results with other real-world evidence from recently published pharmacovigilance studies, are underlying a potential safety signal for remdesivir, which has not been completely evaluated yet, even if very few cases of cardiac arrest, atrial fibrillation, arrhythmia and supraventricular tachycardia have already been observed in the pre-approval trial [ 2 , 10 , 27 ]. The risk of cardiac AEs induced by remdesivir remains largely unknown [ 38 ].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…75% of patients with bradycardia went on to develop serious complications including death. 4 These results were very similar as seen in our study as well.…”
supporting
confidence: 92%
“…A pharmacovigilance study was conducted to assess the association of the use of remdesivir and the risk of reporting serious bradycardia. The results of the study revealed significant association between remdesivir use and the incidence of bradycardia that was mostly serious, highlighting new safety concerns [17] .…”
Section: Discussionmentioning
confidence: 89%